THE INFLUENCE OF INVENTORY MANAGEMENT, PRODUCTION LEAD TIME, AND RAW MATERIAL QUALITY ON COMPANY OPERATIONAL PERFORMANCE - Abu Naim; Nirfison; Abdul Rouf; Eko Hadi Sucipto; Mardi (RADJA PUBLIKA, 2025)
In the era of increasingly intense business competition, companies are required to achieve superior operational performance in order to survive and remain competitive. Operational performance reflects a company’s ability to manage resources effectively to produce goods with high quality, timely delivery, and optimal cost. Several key factors that influence operational performance include inventory management, production lead time, and raw material quality. Poor inventory management can lead to excess stock, increased storage costs, or shortages of raw materials that disrupt production. Long production lead times may cause delivery delays, higher operational costs, and reduced customer satisfaction. In addition, low-quality raw materials can increase defect rates, rework, and waste, thereby reducing operational efficiency. This study aims to analyze the effect of inventory management, production lead time, and raw material quality on company operational performance using a quantitative approach. The research employs a causal associative design to examine the cause-and-effect relationships between the independent variables—inventory management (X1), production lead time (X2), and raw material quality (X3)—and the dependent variable, operational performance (Y). The population consists of employees directly involved in operational activities, including production, warehouse, and quality control departments. Data were collected through questionnaires using a five-point Likert scale and analyzed using SPSS software. Prior to hypothesis testing, validity and reliability tests as well as classical assumption tests (normality, multicollinearity, and heteroscedasticity) were conducted to ensure that the regression model met the BLUE criteria. Multiple linear regression analysis was used to test both partial and simultaneous effects. The results indicate that inventory management and raw material quality have a positive and significant effect on operational performance, while production lead time has a negative and significant effect. Simultaneously, the three variables significantly influence operational performance, with a coefficient of determination of 0.612. These findings suggest that companies should manage inventory effectively, shorten production lead times, and maintain high raw material quality to enhance operational performance. The study provides practical insights for management and serves as a reference for future research in operations management.